Gender Diversity in the Boardroom and the Firm Financial Performance of DSE Listed Companies in Bangladesh - Munira, Shobnom (Global Disclosure of Economics and Business, 2020)
The effect of gender diversity on firm performance is a long debated topic in the business world. The percentage of women representation in the board of directors is comparatively low than women presence in the general population and in the corporate world. Some research suggests board diversity as one of the corporate governance mechanisms that improve firm performance whereas other research suggests the opposite. This study intends to investigate the association between women representation in the boardroom and the companies’ financial performance indicator of Dhaka Stock Exchange (DSE) listed companies in Bangladesh. Total 259 companies’ data from 18 different sectors of DSE are collected from the audited published annual reports. The sample are selected through simple random sampling technique. The data are analyzed using descriptive analysis, correlation analysis and ordinary least square regression method. The study findings indicate that there is positive association between women representation in the boardroom and firm financial performance indicator.